Covid 19 Impact To Regional Economic Growth And International Trade In Indonesia - Eddy Junaidi; Miftakhul Jannah; Khusnudin Tri Subhi; Muhammad Rizki Yudistira (MESP–FEB UNS, 2020)
Covid-19 is a global health problem, including in Indonesia. In Southeast Asia, Indonesia is ranked first in the number of positive cases of Corona since June 17, 2020. Covid-19 cases in Indonesia are increasing every day and on November 9, 2020, the total number of Covid-19 cases in Indonesia is 440,569. The increase in the number of Covid-19 cases had an impact on the economic side where Indonesia's economic growth rate decreased and in the third quarter it was -3.49 percent. In addition, the export and import sectors also experienced decline. This research aims to analyze the impact of Covid-19, exports, imports and investment on Indonesia's economic growth and the impact of Covid-19 and investment on exports and imports in Indonesia. This study uses panel regression analysis with periods of data from the first quarter to the third quarter of 2020. The results show that the Covid-19 case has negative and significant effect on economic growth, while exports, imports and domestic investment do not have significant effect on economic growth. On exports and imports, Covid-19 has negative and significant effect on exports and imports while domestic investment has positive and significant impact on exports and imports in Indonesia.Keywords: Covid-19, growth rate, panel regression, time series